Biomimetic Multiscale Hierarchical Topography Enhances Osteogenic Differentiation of Human Mesenchymal Stem Cells. Issue 14 (13th May 2020) - Yang, Liangliang; Ge, Lu; Zhou, Qihui; Mokabber, Taraneh; Pei, Yutao; Bron, Reinier; van Rijn, Patrick
Abstract: The interface between materials and cells plays a critical role in many biomedical applications. Inspired by the hierarchical architecture of collagen, most abundant structure in the extracellular matrix (ECM), a multiscale hierarchical topography is designed to mimic the collagen nano/micro hierarchical topography. It is hypothesized that the ECM topography affects osteogenesis of human mesenchymal stem cells but until now, it cannot be studied without the biochemical and mechanical influences of the ECM. The multiscale hierarchical topography is achieved by innovatively using sequentially aligned topography preparation via a silicone stretch‐oxidation‐release method and imprinting lithography. The anisotropically hierarchical topography influences stem cell morphology, orientation, and osteogenic differentiation. Intriguingly, the design resembling that of assembled collagen, exhibits the highest degree of osteogenesis. The hierarchical topotaxis effects are further exemplified by the enhanced vinculin expression, cell contractility, and more pronounced nuclear translocation of Yes‐associated protein with the collagen‐mimicking topography, indicative for enhanced osteogenesis. The developed multiscale hierarchical system provides insights into the importance of specific biological ECM‐like topography by decoupling the biochemical influence. Various diseases, cancer, osteoarthritis, and fibrosis display impaired ECM structures, and therefore this system may have a great potential for tissue engineering approaches and developing in vitro disease models. Abstract : A multiscale hierarchical topography is designed and fabricated to mimic the collagen nano/micro hierarchical topography without the biochemical stimulation that is naturally associated with collagen. Intriguingly, the hierarchical topography has a significant influence on the macroscopic behavior and osteogenic differentiation of mesenchymal stem cells and the topography mimicking the complex collagen topography exhibits the highest degree of osteogenesis.